Ground subsidence and its implication on building seismic performance. Issue 126 (November 2019) - Mayoral, J.M.; Tepalcapa, S.; Roman-de la Sancha, A.; El Mohtar, C.S.; Rivas, R.
Abstract: Ground subsidence due to underground water extraction leads to changes in dynamic properties such as shear wave velocity distribution and shear modulus degradation and damping curves, and more importantly, soil layer thickness and shape. These effects modify site predominant periods, frequency content, and spectral accelerations in both the free field and soil-structure systems during an earthquake. These variations can be substantial in highly compressible very soft clays, such as those found in the Mexico City basin. This paper examines the complex role that ground conditions, including settlement variability and structural tilting due to regional ground subsidence, had in the seismic performance of buildings during the Mw 7.1 2017 Puebla-Mexico City earthquake. A numerical study was undertaken to simulate the seismic response of conventional buildings supported by a compensate box-like foundation in soft clay, representative of those that exhibited major damage or collapse. Sets of three-dimensional finite difference models were developed with FLAC 3D . Initially, the overall static behavior of the soil-structure system was assessed, considering both ground settlement and structure tilting due to ground consolidation, resembling the conditions prevailing right before the earthquake. Then, the seismic performance evaluation during the dynamic event was conducted at several consolidation times (i.e. 0, 25, 32 and 45 years). From the results gathered herein, it was clearly established the effect of the variation of the fundamental period of the soil deposit, and the initial ground deformation and structural tilting, on the seismic demand acting on the structure during the earthquake, which in turn, lead to most of the observed failures. Graphical abstract: Image 1 Highlights: About 63% of collapses during the September 19, 2017 earthquake were related to geotechnical aspects. This damage is associated to building performance evolution over time. Soil stresses variation leads to ground deformation, building tilting, and changes in dynamic properties. Variation of site period, ground deformations, and building tilting, controls the seismic demand. Seismic demand effects were accentuated in poorly-maintained or improperly design or constructed buildings.